Identifikasi Tingkat Stres Peserta Didik Menjelang Ujian Nasional Pada Jenjang Pendidikan Menengah - Paul Arjanto (Universitas Kanjuruhan Malang, 2016)
National exam raises various demands. Learners feel required to achieve achievement (achievement). This demand may put pressure potentially cause stress on self-learners. Stress experienced by learners in light levels makes the students eager to learn the national exams, but in the later stages of stress can lead to complaints from learners. Objective is to identify the stress level of students for national exams secondary education. This research use descriptive research with quantitative approach (descriptive research). The research instrument to measure the level of stress based on the symptom / symptoms of individuals who experience stress using the instrument DASS (Depression Anxiety Stress Scale). The results showed 8% of learners experiencing severe stress, 24% of students experience stress on a moderate, 50% of learners are having on the stage light and 18% of students experience stress on a normal level and there are learners who experience stress at levels very heavy. Researchers suggest: 1) expanding the number of research subjects so that they can generalize research data, 2) controlling other factors which can influence the stress levels of learners such as social support from family, the role of teacher mentoring in schools, as well as the personality of learners who are vulnerable to stress.